Saliva as a future potential predictor for various periodontal diseases - Zahreni Hamzah (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2011)
Background: There are many diagnostic biomarkers have been found in saliva. Saliva contains a wide variety of proteins, including bacteria and products, enzymes, inflammatory mediators and host response modifiers, products of tissue breakdown. Purpose: The purpose of the study was studied current development of diagnostic biomarkers in saliva that will lead to the development of simple and accurate diagnostic tools for periodental disease. Reviews: Specifically, the salivary biomarkers divided for three aspects of periodontitis i.e. inflammation, collagen degradation and bone turnover, correlated with clinical features of periodontal disease. The diagnostic biomarkers is in saliva, such as enzyme, immunoglobulin, cytokines, bacteria and bacterial products, hormones. For the past two decades, oral health researchers have been developing salivary diagnostic tools to monitor oral diseases. Conclusion: The indicators of acute periodontitis can detect with ß-glucuronidase and AST, IL-1β, and MMP-8, whereas indicators for chronic periodontitis can detect with ALP. The indicators for collagen degradation and bone turnover suggest ICTP, fibronectin fragments, and osteonectin. The indicators of severity of periodontitis especially can be predict by B. forsythus.Latar belakang: Banyak biomarker telah ditemukan dalam saliva. Saliva terdiri dari berbagai protein unik meliputi bakteri dan produk bakteri, enzim, mediator inflamasi dan modifikasi respon host (immunoglobulin, sitokin), produk kerusakan jaringan (telopeptida kolagen, osteokalsin, proteoglikan, fragmen fibronectin). Tujuan: Mengkaji biomarker dalam saliva untuk pengembangan metode diagnostik sederhana dan akurat untuk penyakit periodontal. Tinjauan Pustaka: Secara khusus, biomarker saliva pada periodontitis dibagi dalam tiga aspek yaitu inflamasi, dan degradasi kolagen serta pergantian tulang. Biomarker diagnostik dalam saliva, meliputi enzim, imunoglobulin, sitokin, bakteri dan produk-produk bakteri, hormon. Selama dua dekade terakhir, para peneliti kesehatan mulut telah mengembangkan alat diagnostik melalui saliva yang tepat untuk memonitor beberapa penyakit periodontal. Kesimpulan: Indikator periodontitis akut dapat dideteksi dengan β-glucuronidase dan AST, IL-1β,dan MMP-8, whereas indikator untuk periodontitis kronis dapat dideteksi dengan ALP. Indikator untuk degradasi kolagen dan penggantian tulang dideteksi melalui ICTP, fibronectin fragments, dan osteonectin. Sedang indikator untuk keparahan periodontitis terutama dapat diprediksi melalui B. forsythus.